2020
DOI: 10.1371/journal.pone.0242260
|View full text |Cite
|
Sign up to set email alerts
|

Integration of small RNA, degradome and proteome sequencing in Oryza sativa reveals a delayed senescence network in tetraploid rice seed

Abstract: Seed of rice is an important strategic resource for ensuring the security of China's staple food. Seed deterioration as a result of senescence is a major problem during seed storage, which can cause major economic losses. Screening among accessions in rice germplasm resources for traits such as slow senescence and increased seed longevity during storage is, therefore, of great significance. However, studies on delayed senescence in rice have been based mostly on diploid rice seed to date. Despite better tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In the present study, small RNAs from A. donax plants were sequenced and known as well as candidate novel miRNAs were identified. The obtained sRNA profiles were consistent with the typical ones reported for rice, wheat, and other monocots [ 43 , 49 , 50 , 51 ], where the 24-nt sRNAs are the most abundant and heterogeneous class of small non-coding RNAs in the sRNAs libraries, while the 21-nt sRNAs, being mostly miRNA sequences, show a low level of redundancy. Consistently with the general characteristic of miRNAs [ 39 ] and with previous reports on A. donax [ 48 ] and other plants [ 43 , 52 ], we observed a miRNA length distribution with a prevalence of 21-nt sequences followed by those of 20-nt in length.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, small RNAs from A. donax plants were sequenced and known as well as candidate novel miRNAs were identified. The obtained sRNA profiles were consistent with the typical ones reported for rice, wheat, and other monocots [ 43 , 49 , 50 , 51 ], where the 24-nt sRNAs are the most abundant and heterogeneous class of small non-coding RNAs in the sRNAs libraries, while the 21-nt sRNAs, being mostly miRNA sequences, show a low level of redundancy. Consistently with the general characteristic of miRNAs [ 39 ] and with previous reports on A. donax [ 48 ] and other plants [ 43 , 52 ], we observed a miRNA length distribution with a prevalence of 21-nt sequences followed by those of 20-nt in length.…”
Section: Discussionsupporting
confidence: 87%
“…By analyzing the microRNAs degradome sequencing results in O. sativa , researchers found that the expression of miR164d has changed significantly in tetraploid rice. miR164d regulates the antioxidant enzyme gene through its target gene Os12g0610600 (NAC domainā€containing protein 21/22), and Os12g0610600 interact with gene Os04g0573200 (copper chaperone for superoxide dismutase, chloroplasticā€like, CCS), which may be the reason for the delayed senescence of polyploid rice seeds 60 . Moreover, miR164 delayed the senescence of strawberry fruit ( Fragaria ananassa ) under low temperature by negatively regulating the expression of NAC transcription factor genes 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics research has shown that the translation of multiple genes is changed in the tetraploid genotype compared with the diploid genotype [ 39 , 40 ]. For example, compared to diploid rice, tetraploid rice had more CAT proteins, peroxidase P7, and catalase isozyme A [ 41 ]. Autotetraploid P. australis exhibited a higher expression of protein genes related to glutathione metabolism, cell division, and chlorophyll, cellulose, and lignin synthesis than the diploid genotype [ 42 ].…”
Section: Discussionmentioning
confidence: 99%